English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1) x - (2x - 8) = 3x - 2(x + 5)
2) x - (2x - 6) = 3x - 2(x + 5)
Please provide all the work.

2006-12-04 06:20:45 · 7 answers · asked by katlover118 2 in Science & Mathematics Mathematics

7 answers

1) x - (2x - 8) = 3x - 2(x + 5)

So x - 2x + 8 = 3x - 2x - 10
ie -x + 8 = x - 10

So -x + x + 8 + 10 = x + x - 10 + 10
ie 18 = 2x

So x = 9

2) x - (2x - 6) = 3x - 2(x + 5)
ie x - 2x + 6 = 3x -2x - 10

ie -x + 6 = x - 10

So -x + x + 6 + 10 = x + x - 10 + 10
ie 16 = 2x

So x = 8

2006-12-04 06:26:03 · answer #1 · answered by Wal C 6 · 1 1

1. X-2x+8=3x-2x-10
-X+8=x-10
-2X=-18
2X=18
X=9
2. X-2X+6=3X-2X-10
-X+6=X-10
-2X=-16
2X=16
X=8

2006-12-04 06:32:28 · answer #2 · answered by Tony T 4 · 1 0

x -(2x - 8) = 3x - 2(x + 5)

x -2x + 8 = 3x - 2x - 10

-x + 8 = x - 10

- x + 8 + x = x - 10 + x

8 = 2x - 10

8 + 10 = 2x

18 = 2x

18/2 = 2x/2

9 = x

The answer is x = 9

- - - - - - -- - - - - - - - - - -

x - (2x - 6) = 3x - 2(x + 5)

x -2x + 6 = 3x - 2x - 10

- x + 6 = x - 10

- x + 6 + x = x - 10 + x

6 = 2x - 10

6 + 10 = 2x - 10 + 10

16 = 2x

16/2 = 2x/2

8 = x

The answer is x = 8

- - - - - -s-

2006-12-04 07:11:18 · answer #3 · answered by SAMUEL D 7 · 1 0

1)
x - (2x - 8) = 3x - 2(x + 5)
x - 2x + 8 = 3x - 2x - 10
x = 3x - 18
2x = 18

x = 9

2)
x - (2x - 6) = 3x - 2(x + 5)
x - 2x + 6 = 3x - 2x - 10
x + 6 = 3x - 10
2x = 16

x = 8

2006-12-04 06:44:07 · answer #4 · answered by Luiz S 7 · 1 0

1) x - (2x - 8) = 3x - 2(x + 5)
....x - 2x + 8 = 3x - 2x - 10
...-x + 8 = x - 10
... 18 = 2x
.. 9 = x

2) almost exactly like it.

2006-12-04 06:27:33 · answer #5 · answered by Philo 7 · 0 0

http://www.algebrahelp.com/calculators/equation/

this will give you the work

1) x=9
2) x=8

2006-12-04 06:27:45 · answer #6 · answered by Melissa R 2 · 0 0

No, that's your job. Look in your textbook.

2006-12-04 06:27:55 · answer #7 · answered by parsonsel 6 · 0 0

fedest.com, questions and answers